EFFECTS OF SANYINJIAO ACUPRESSURE AND CINNAMON DECOCTION DYSMENORRHEA ADOLESCENTS’ MEAN PLATELET VOLUME - Indah Sari; Nyna Puspita Ningrum; Nina Hidayatunnikmah (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
Introduction: Dysmenorrhea is a common menstrual pain complaint among adolescent girls affecting physical, psychological, and social activities. According to the World Health Organization (WHO) in 2021, 90% of women worldwide experience dysmenorrhea, and approximately 10–15% suffer from severe cases. One of the biological indicators related to menstrual pain is Mean Platelet Volume (MPV), the average size of platelets in the blood and reflects platelet activity and inflammation. The normal range of MPV is 150.000–400.000 µL, and elevated values may indicate an inflammatory process or acute pain, such as in dysmenorrhea. Objective: To determine the effect of the combination of Sanyinjiao (SP6) acupressure and cinnamon decoction on Mean Platelet Volume (MPV) levels before and after treatment in adolescent girls with dysmenorrhea. Methods: This study used a Pre-Experimental design with a One Group Pre-test and Post-test approach. The sample consisted of 32 adolescent girls with dysmenorrhea, selected using total sampling. The intervention of Sanyinjiao (SP6) acupressure and cinnamon decoction was administered twice daily for five days during menstruation. Results: The mean value of MPV showed a decrease after the intervention, with a p-value of 0.000 (<0.05), indicating a significant effect of the combination of Sanyinjiao (SP6) acupressure and cinnamon decoction on reducing MPV levels in adolescents with dysmenorrhea. Conclusions: The combination of SP6 acupressure and cinnamon decoction was proven to be effective in significantly reducing MPV levels in adolescent girls with dysmenorrhea. This therapy may serve as a practical and safe non-pharmacological alternative to alleviate menstrual pain associated with inflammation.